Bonding Strength Between Steel and Concrete Through Incorporation of 20% Palm Oil Fuel Ash (POFA) and Expanded Polystyrene (EPS) - Bakhary, Arief Firdaus; Osman, Mohamad Hairi (Progress in Engineering Application and Technology, 2023)
In general, palm oil fuel ash (POFA) was a by-product of the production of cooking oil. POFA comprising pozzolanic material that has little or no cementitious value but, in finely divided form and in the presence of moisture, will chemically react with calcium hydroxide at ordinary temperatures to generate cementitious compounds. With these features, the concrete binder will be increased indirectly. Using POFA as a replacement is one way to make cement more environmentally friendly, given that POFA is derived from an organic substance. This study’s primary objective was to discover if POFA and EPS are suitable for use in concrete. It focused on the bonding strength between straight steel bars and concrete, as well as the usage of expanded polystyrene (EPS) and palm oil fuel ash (POFA) as concrete alternatives. This experiment substituted 10% to 30% of the fine aggregate volume in the concrete mixture with expanded polystyrene (EPS). In contrast, 20% of the cement mass in the concrete mixture was replaced with POFA. The binding strength of EPS-POFA concrete and steel bar was measured using a pull-out test. The mechanical properties of POFA were examined using the compressive test and compared to cement. The performance of the EPS and POFA-containing concrete was then compared to that of standard concrete. Thus, the ideal replacement percentage for EPS and POFA was determined. Based on research findings, the bonding performance will increase when the POFA is present.